MAPPADDEKKO: PENGUATAN SOLIDARITAS BERBASIS TRADISI BAGI PETANI DI DESA KALEBAREMBENG KABUPATEN GOWA - Rahman, Abdul; Tungkagi, Donald Qomaidiansyah (Universitas Negeri Makassar, 2024)
The people of Kalebaremeng Village are people who remain firm in maintaining traditions amidst the development of modern life. One tradition that has survived to this day is mappaddekko. This article aims to elaborate on the function of mappaddekko, especially when it is related to efforts to strengthen solidarity. The method used in this research is a qualitative research method. Data was collected by means of observation and interviews. Observations were made by looking at the implementation of mappadekko, starting from the preparatory stage to the end of implementation. The results of these observations were then strengthened by conducting interviews with the community, traditional leaders, and the village government. Furthermore, the data were analyzed by utilizing relevant theories and research results. The results of the study show that mappaddekko among the people of Kalebaremeng Village, which has an agrarian pattern, is still being implemented today because it functions as an arena to strengthen social relations and strengthen bonds of solidarity regardless of social status. This tradition is carried out on the basis of a mutual agreement, in which there are no exploiting or exploited parties in its implementation.